Interobserver variability (between radiation oncologist and radiation therapist) in tumor bed contouring after breast-conserving surgery. Issue 3 (June 2019) - La Rocca, Eliana; Lici, Vanessa; Giandini, Tommaso; Bonfantini, Francesca; Frasca, Sarah; Dispinzieri, Michela; Gennaro, Massimiliano; Di Cosimo, Serena; Lozza, Laura; Pignoli, Emanuele; Valdagni, Riccardo; De Santis, Maria Carmen
Purpose: To examine interobserver variability between the radiation oncologist (RTO) and the radiation therapist (RTT) in delineating the tumor bed (TB) in early breast cancer (BC). Methods: We retrospectively analyzed patients who received a radiotherapy boost to the TB. In a first group, the clinical target volume (CTV) for the boost was the surgical bed, defined by using surgical clips. In a second group, the CTV was defined by identifying a seroma cavity or a metallic find on the scar. These contours were compared in terms of volume, number of slices, and Dice similarity coefficient (DSC). Results: Forty patients were assessed: 20 had surgical clips (group 1) while the other 20 had none (group 2). There was no difference in the number of slices contoured by the 2 operators for group 1, but a statistically significant difference emerged in the volumes: the RTT identified a TB that was a mean 45% smaller than the one identified by the RTO. Random differences were found between the 2 operators for group 2. The TBs delineated for this group were significantly larger ( P <0.05) than those identified by the RTT for group 1. The mean Dice value between the RTO's and the RTT's TBs was 0.69±0.07 (range 0.53–0.81) for group 1 and 0.37±0.18 (range 0–0.58) for group 2 ( P <0.05). Conclusions: This study showed that the use of clips coincided with less interoperator variability. With appropriate training, the RTT may play an important part in the multidisciplinary radiotherapy team.